Shinier cows, more and better milk, income increase: First results of co-designing silage technology with a women farmer group in Tunisia - Rudiger, Udo (CGIAR System Organization, 2023)
Small-scale livestock farmers in Central Tunisia are suffering from scarcity of feed resources and increasing feed prices. Since the beginning of the Ukraine war, prices for feed concentrates have significantly increased from about 350 $ / ton to almost 500 $ / ton. In addition, the extreme drought of the last agricultural season 2022-2023 has increased prices of other feed resources like straw and hay by 30% while milk prices, fixed by the Tunisian government, remain unchanged. This situation has reduced profitability of dairy farmers to such an extent that some farmers abandon milk production leading to milk shortage in the Tunisian markets. An alternative feed resource that is less expensive than feed concentrates and important for increasing milk quality and quantity is silage. Silage is grass that has been 'pickled'. It is a method used for conserving fresh grass, legumes, or green forage for ruminants. The grasses are cut, compacted, and stored and fermented in anaerobic conditions. Silage could therefore be an interesting option for dairy farmers to keep forage in good conditions for a long time and provide high-quality ruminant feed for increasing profitability. The agroecology Initiative in Tunisia has co-design technical innovations with farmers within an Agroecological Living Landscape (ALL). One of the actors of the ALL is a women farmer group in the village of Sers in central Tunisia. The group is composed of about 50 women engaged in livestock and dairy production. During participatory visioning exercises, the issue of reduced profitability of milk production has been raised by the farmers. ICARDA and its national partner organization OEP (livestock and pasture office) proposed silage technology, which hasn’t been known by the farmers yet. The co-designed experiment showed an increase in milk production and income when dairy farmers are using silage as additional feed.